On Taxation in a Two-Sector Endogenous Growth Model with Endogenous Labor Supply - Paul A. de Hek (Tinbergen Institute, 2003)
This paper examines the effects of taxation on long-run growthin a two-sector endogenous growth model with (i) physical capitalas an input in the education sector and (ii) leisure as anadditional argument in the utility function. The analysis of theeffects of taxation - including income taxation, capital incometaxation and labor income taxation - distinguishes between thecase with a unique (interior) balanced growth path and the casewith multiple balanced growth paths. Due to the flexibility oflabor supply, taxation of income may induce agents to spend moreor less time on leisure activities. In the case of incometaxation, where capital and labor income are taxed equally, theresulting effect on the growth rate is negative. The contributionof endogenous leisure is confined to reducing or increasing thesize of the effect on the growth rate. If only capital income istaxed, the direction of the effect may reverse. In that case, thepositive effect of the increase in total non-leisure timedominates the direct negative effect, implying that capitaltaxation increases the long-run growth rate.
Keywords: E20; H20; J22; J24; O41; 330; Taxation; Endogenous growth; Endogenous labor supply.; Neue Wachstumstheorie; Steuer; Steuerwirkung; Theorie